Whole body vibration on taxi driver - Muhammad Syafik, Isa (2012)
This thesis is entitled about the Whole Body Vibration on Taxi Driver at two highways which is South-North Highway and Kuala Lumpur-Karak Highway. Usually, taxi driver are sitting on the seat while they are driving for the whole working times. Additionally, long duration of exposure to whole body vibration while driving may lead them to have diseases and adverse health especially lower back pain. The objective of this study is to measure and record, vibration exposures in the x, y, z axis directions to which occupational taxi drivers are exposed measured. Vibration will be reported as root mean square (r.m.s) unit of m/s2. All the respondents which is taxi drivers had given a questionnaire in order to indicate the prevalence, severity and the human sensation that would lead to musculoskeletal disorders and lower back pain, thus all collected data will be compared to the exposure limit standard which ISO 2631.. . From the measurement, it has found that the taxi driver that through Kuala Lumpur-Karak Highway daily exposure to vibration A(8) and Vibration Dose Value (VDV) were 0.4166 m sec-2 and 7.5871 m sec-1.75, while for the taxi driver that through North-South Highway were 0.3917 m sec-2 and 7.1438 m sec-1.75 respectively. It can be concluded that whole body vibration absorbed by the taxi driver has not been exceeding RMS minimum exposure value that could lead adverse health to taxi driver in term of long duration.